HUBUNGAN STATUS GIZI DENGAN TINGKAT KESEGARAN JASMANI SISWA SEKOLAH DASAR NEGERI 18 SUMBER JAYA KABUPATEN BENGKALIS - Wiyono Wiyono; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, Problems in this study originated from the observation of the author encountered in the field, it is still low physical fitness of students of SD Negeri 18 Sumber Jaya Bengkalis. The purpose of this study was to determine the nutritional status contribute to the physical fitness of male students SD Negeri 18 Sumber Jaya Bengkalis. This type of research is correlational. The population in this study was 18 Sumber Jaya Elementary School Bengkalis totaling 72 people using purposive technique side where the student population sampled is predetermined or with certain considerations which totaled 23 people, to get the research data used test TKJI , and BMI for nutritional status. Data were analyzed with a simple product moment. Based on the results of my research has been described in the previous chapter can be stated the following conclusion: There is a significant relationship between nutritional status (X) to physical fitness (Y) students of SD Negeri 18 Sumber Jaya Bengkalis, obtained rhitung = 0.52> rtabel = 0.413.Keywords : Nutritional Status, Physical Fitness